Laminar burning velocity and ignition delay time for premixed isooctane–air flames with syngas addition. Issue 2 (4th March 2017) - Bhattacharya, Atmadeep; Datta, Amitava; Wensing, Michael
Abstract : The effects of blending syngas in different proportions to isooctane on the laminar burning velocity and ignition delay time of the fuel–air mixture have been studied in SI engine relevant conditions. The syngas is assumed to be composed of 50% H2 and 50% CO. Simulations have been carried out using a skeletal mechanism containing 143 species and 643 reaction steps. It has been found that the blending of syngas augments the laminar burning velocity of isooctane due to increase of the thermal diffusivity of the reactant mixture and alteration in the chemistry of the flame reactions. For the mixture of 30% isooctane/70% syngas, the laminar burning velocity and the ignition delay time values are very close to those corresponding to pure isooctane. Additionally, the effects of exhaust gas recirculation have been explored for the 30% isooctane/70% syngas–air flame. It is seen that the reduction in laminar burning velocity due to the dilution by the recirculated exhaust gas can be compensated by an increase in the unburnt gas temperature. The effect of the exhaust gas dilution on the ignition delay time of 30% isooctane/70% syngas–air mixture has been found to be negligible.